The Risk Factors for Stunting in Children Aged 6-59 Months: A Study of Case Control in A Sub Urban Area - Kusumaningati, Walliyana; Dainy, Nunung Cipta (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Indonesia currently has a high incidence of stunting. The stunting prevalence in Bogor Regency is 28,6%, which is higher than the national stunting prevalence. Padasuka Village is categorized as sub-urban. Factors causing stunting can differ depending on the characteristics of the area. The objective of the study was to analyze the factors that cause stunting in children aged 6-59 months in sub-urban areas. Observational research method with case control design was conducted from December 2022 to June 2023. The research location was Padasuka Village, Bogor Regency. Data on children under five years old were weight, height, history of infectious diseases, exclusive breastfeeding, immunization, macro and micronutrient intake and maternal knowledge. Data were collected using a questionnaire with interview techniques. Nutrient intake data were obtained using a 2x24 hour food recall form. The study sample sizes were 41 cases and 41 controls, making a total of 82 subjects. Statistical analysis using SPSS 16 for Windows software used univariate analysis to see the description of each research variable and analysis of the relationship between variables (bivariate) using the Chi-Square test for characteristic data and independent t-test for intake data. The results of the analysis were birth weight (p-value=0,012), birth length (p-value=0,012), energy intake (p-value=0,002), carbohydrate intake (p-value=0,024), and protein intake (p-value=0,037) had significant differences between the stunting group and the normal group. Birth weight, birth length, energy intake, carbohydrate intake, and protein intake are risk factors for stunting in children under five years old in sub-urban areas.